Pengembangan Media Pembelajaran Berbasis Android pada Masa Pandemi Covid-19 untuk Meningkatkan Literasi Sains Peserta Didik - Ramdani, Agus; Jufri, A. Wahab; Jamaluddin, Jamaluddin (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
This study aims to develop a feasible Android-based learning media to increase students' scientific literacy. This research uses the Four D model procedure. In addition to developing android-based media, this research also develops syllabus, lesson plans, and scientific literacy instruments. This research was conducted at one of the junior high schools in the city of Mataram. Validation of Android-based learning media was carried out by three validators of media experts and material experts. Expert validation data analysis was performed using the Pearson validation formula. The results of the feasibility study for Android-based learning products showed the validity of 84% with very valid criteria. The results of the media feasibility study obtained an average score of 88%, the syllabus obtained an average score of 83%, lesson plans obtained an average score of 82%, and the scientific literacy instrument obtained an average score of 83%. In conclusion, Android-based media products on natural science material can be implemented in learning, especially during the Covid-19 pandemic.